Blockchain Technology for Enhancing Traceability and Sustainability in Fish and Fishery Products: Comprehensive Review - Veena, M.; Sravani, K.; Dhanapal, K.; Kumar, G. Praveen; Manaswini, C.; Basha, D. Chand (International Journal of Bio-resource and Stress Management, 2025)
This study was done to ensure effective fisheries management while protecting marine ecosystems and livelihoods by integrating traceability and sustainability practices. Fisheries played a crucial role in food security worldwide, supporting millions of livelihoods and providing nutrition for billions. However, challenges like overfishing, Illegal fishing, and environmental degradation threatened marine ecosystems. Traceability and sustainability were vital to addressing these issues by combating Illegal, Unreported and Unregulated (IUU) fishing, ensuring food safety, supporting sustainable practices, and meeting regulatory requirements. The fish industry experienced substantial illegal, unreported, and unregulated (IUU) activities within traditional supply chain systems. Blockchain technology and the Internet of Things (IoT) were expected to transform the fish supply chain (FSC) by incorporating distributed ledger technology (DLT) to build trustworthy, transparent, decentralized traceability systems that promoted secure data sharing and employed IUU prevention and detection methods. Efficient traceability management was necessary for managing products in the fishery supply chain. Monitoring and tracking of the fishery supply chain operations assisted system stakeholders in identifying the origins and causes of product fraud and malpractice. Traceability helped prevent IUU fishing, which costs up to 23.5 billion annually, by using blockchain systems to record catch data immutably and enable real-time tracking. Technologies like RFID (Radio Frequency Identification tags) and QR (Quick Response) codes verified seafood origin, reducing fraud and enhancing food safety. Sustainability prevented overfishing, preserved biodiversity, and supported small-scale fishers through fair trade practices. With 75% of consumers favouring sustainably sourced seafood, blockchain enhanced trust by providing transparent sustainability records and QR code verification.